The Information Society in Europe: Policies to Stem the Digital Divide - Armas Quintá, Francisco José; Macía Arce, José Carlos (Quaestiones Geographicae, 2013)
A Digital Agenda for Europe is one of the seven flagship initiatives of the Europe 2020 Strategy. The main objective of this initiative consists of promoting ICT, especially the Internet, as a strategic tool to improve business, healthcare services, transport and social activity in a better global standard-of-living context. The Europe 2020 Strategy recommends broadband access for all European citizens by 2013 and higher Internet speeds (30 Mbps or above) by 2020. Nevertheless, what is the real position in the European regional and urban context? This article attempts to describe and explain the current situation and trends in relation to the Europe 2020 Strategy initiative.